Evaluation von Standards und Evaluation für Standards. Zentraler Tagungsband der 15. Hochschultage Berufliche Bildung - Beutner, Marc (Qualität in Schule und Betrieb. Forschungsergebnisse und gute Praxis)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

The Frontiers of the Sea - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

A Nose By Any Other Name - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

Imitators and optimizers in a changing environment - Hehenkamp, Burkhard; Kaarbøe, Oddvar M. (Journal of Economic Dynamics and Control)

Phonon-assisted tunneling between singlet states in two-electron quantum dot molecules - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review B)
We study phonon-assisted electron tunneling in semiconductor quantum dot molecules. In particular, singletsinglet relaxation in a two-electron-doped structure is considered. The influence of Coulomb interaction is discussed via comparison with a single-electron system. We find that the relaxation rate reaches similar values in the two cases but the Coulomb interaction shifts the maximum rates toward larger separations between the dots. The difference in electron-phonon interaction between deformation potential and piezoelectric coupling is investigated. We show that the phonon-induced tunneling between two-electron singlet states is a fast process, taking place on the time scales of the order of a few tens of picoseconds.
Keywords: tet_topic_qd

Molecular dynamics simulation of defect formation and precipitation in heavily carbon doped silicon - Zirkelbach, F.; Lindner, Jörg; Nordlund, K.; Stritzker, B. (Materials Science and Engineering: B)
The precipitation process of silicon carbide in heavily carbon doped silicon is not yet fully understood. High resolution transmission electron microscopy observations suggest that in a first step carbon atoms form C Si dumbbells on regular Si lattice sites which agglomerate into large clusters. In a second step, when the cluster size reaches a radius of a fewnm, the high interfacial energy due to the SiC/Si lattice misfit of almost 20% is overcome and the precipitation occurs. By simulation, details of the precipitation process can be obtained on the atomic level. A recently proposed parametrization of a Tersoff-like bond order potential is used to model the system appropriately. Preliminary results gained by molecular dynamics simulations using this potential are presented.

Transition between different coherent light–matter interaction regimes analyzed by phase-resolved pulse propagation - zu Siederdissen, Tilman Höner; Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Khitrova, Galina; Gibbs, Hyatt M.; Koch, Stephan W.; Giessen, Harald (Optics Letters)
We present phase-resolved pulse propagation measurements that allow us to fully describe the transition between several light–matter interaction regimes. The complete range from linear excitation to the breakdown of the photonic bandgap on to self-induced transmission and self-phase modulation is studied on a high-quality multiple-quantum-well Bragg structure. An improved fast-scanning cross-correlation frequency-resolved optical gating setup is applied to retrieve the pulse phase with an excellent signal-tonoise ratio. Calculations using the semiconductor Maxwell–Bloch equations show qualitative agreement with the experimental findings.
Keywords: tet_topic_polariton; tet_topic_qw

Theoretical study of phononassisted singlet-singlet relaxation in two-electron semiconductor quantum dot molecules - Grodecka, Anna; Machnikowski, Paweł; Förstner, Jens (physica status solidi (c))
Phonon-assisted singlet-singlet relaxation in semiconductor quantum dot molecules is studied theoretically. Laterally coupled quantum dot structures doped with two electrons are considered. We take into account interaction with acoustic phonon modes via deformation potential and piezoelectric coupling. We show that piezoelectric mechanism for the considered system is of great importance and for some ranges of quantum dot molecule parameters is the dominant contribution to relaxation. It is shown that the phonon-assisted tunneling is much faster (down to ∼ 6 ps even at zero temperature) in comparison with other decoherence processes. The influence of Coulomb interaction is discussed and its consequences are indicated. We calculate the relaxation rates for GaAs quantum dot molecules and study the dependence on quantum dot size, distance and offset between the constituent quantum dots. In addition the temperature dependence of the tunneling rates is analyzed.
Keywords: tet_topic_qd

Zahlungsbereitschaften für Geschäftsmodelle produktbegleitender Dienstleistungen --- Wirtschaftlichkeit bei der Vermarktung hybrider Produkte - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Weddeling, Matthias (Technologie und Dienstleistung: Innovationen in Forschung, Wissenschaft und Unternehmen Beiträge der 7. Dienstleistungstagung des BMBF)

Ordnungsrahmen für die hybride Wertschöpfung - Becker, J; Beverungen, Daniel; Knackstedt, R; Glauner, C; Stypmann, M; Rosenkranz, C; Schmitt, R; Hatfield, S; Schmitz, G; Eberhardt, S; Dietz, M; Thomas, O; et al. (Dienstleistungsmodellierung --- Methoden, Werkzeuge und Branchenlösungen)

Wertschöpfungsnetzwerke von Produzenten und Dienstleistern als Option zur Organisation der Erstellung hybrider Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Wertschöpfungsnetzwerke --- Konzepte für das Netzwerkmanagement und Potenziale aktueller Informationstechnologien)

Konzeption einer Modellierungssprache zur softwarewerkzeugunterstützten Modellierung, Konfiguration und Bewertung hybrider Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Dienstleistungsmodellierung --- Methoden, Werkzeuge und Branchenlösungen)

Stammdatenkonzept für elektronische Verkaufsförderungsaktionen im Wertschöpfungsdreieck Hersteller, Händler und Kunde - Becker, Jörg; Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian (Wertschöpfungsnetzwerke: Konzepte für das Netzwerkmanagement und Potenziale aktueller Informationstechnologien)

Trennung von Netz und Betrieb als Königsweg? Pfadabhängigkeiten der Regulierung - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (BDI-Bundesnetzagentur-Regulierungskonferenz 2008)
Die Trennung von Netz und Betrieb steht nicht nur im Zentrum der politischen Debatte der Energiewirtschaft. Auch im Bahnsektor ist die Privatisierung mit oder ohne Netz ein heiß diskutiertes Thema. Und selbst in der Telekommunikation strebt die EU-Kommission eine weitgehende Entflechtung an. Der vorliegende Beitrag entwickelt anhand von ökonomischen Kriterien ein ideologiefreies Prüfschema, wann eine Entflechtung von Netz und Betrieb gesamtwirtschaftlich vorteilhaft ist und wann nicht.

Export production under exchange rate uncertainty - Broll, Udo; Gilroy, Bernard Michael; Lukas, Elmar

Small-and Medium-sized Enterprises (SMEs) in internationally operating R&D networks: recent findings and trends - Gilroy, Bernard Michael; Baier, Melanie; Lukas, Elmar (International Journal of Globalisation and Small Business)

Die Funktionen eines Patentsystems und ihre Bedeutung für Unternehmensausgründungen aus Hochschulen - Gilroy, Bernard Michael; Volpert, Tobias (Open Source)

A longitudinal panel study on antecedents and outcomes of work-home interference. - Steinmetz, Holger; Frese, M; Schmidt, P (Journal of Vocational Behavior.)

Human needs as predictors for organizational commitment and job involvement: An exploratory empirical study. - Park, Y K; Lee, C I; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)